(untitled) (Colombia Medica, 2024)
Background: Evidence-based practice (EBP) is a systematic approach to professional practice using the best available evidence to make informed clinical decisions in healthcare. It is necessary to measure and identify strengths and opportunities for improvement. Objective: To assess the knowledge and application of EBP in respiratory health professionals in Latin America. Methods: A cross-sectional study was conducted. The questionnaire was distributed online to health professionals in Latin American countries. Demographic data, professional characteristics, EBP training, and questionnaire responses were collected. Descriptive and inferential statistical analyses were performed. Results: A total of 448 respiratory health professionals participated in the study. Responses were obtained from 17 countries where the majority were female, with an average age of 42. Participants included physicians, physiotherapists, nurses, respiratory therapists, speech therapists, and occupational therapists. Overall scores indicated moderate to high levels of EBP knowledge and application. However, variations were observed in different dimensions. Factors such as EBP training, reading scientific articles, and professional characteristics were associated with higher scores. Barriers to implementing EBP were identified mostly related to institutional support. Conclusions: This study provides information on the knowledge and implementation of EBP in respiratory health professionals in Latin America. Although the overall levels of knowledge and application of EBP were moderate to high, there are options for improvement, especially in addressing barriers to implementation.